Analysis of Factors Causing Bankruptcy Using the Altman Z-Score Model (Case Study of PT Sepatu Bata Tbk 2019-2023) - Naura Salsabilla; Wastam Wahyu Hidayat; Supardi Supardi (Jurnal Restorasi : Hukum dan Politik, 2025)
This rsearch aims to analyze the factors causing the bankruptcy of PT Sepatu Bata Tbk during the 2019-2023 period using the Altman Z-Score model. A quantitative descriptive approach with secondary data from the company's annual financial reports and supporting information from the company's official website was used in this study. The Altman Z-Score analysis results for PT Sepatu Bata Tbk show a significant decline in financial health from 2019 to 2023, shifting from a safe zone to a distress zone, indicating a high risk of bankruptcy. The main causes are internal factors such as poor working capital management (X1), continuous operating losses (X3), and an imbalanced capital structure (X4), exacerbated by a decrease in retained earnings (X2) and asset efficiency (X5). This potential bankruptcy has a broad impact on all stakeholders, including employees, suppliers, consumers, investors, creditors, as well as management and owners, thus strategic and rapid restructuring is highly necessary.